Risk factors for nosocomial rectal colonisation with carbapenem-resistant Gram-negative bacilli in children with haematological malignancies: a case-control study - Chao Fang; Zheng Zhou; Mingming Zhou; Jianping Li (BMC, 2023)
Abstract Background Rectal colonisation with carbapenem-resistant Gram-negative bacilli (CR-GNB) may cause CR-GNB infection in children with haematological malignancies (HMs) haematological. To date, information on its epidemiology is limited. This study aimed to assess the the risk factors for rectal colonisation with CR-GNB in children with HMs. Methods A case-control study in a tertiary children's hospital in Hangzhou City, was conducted between July 2019, and September 2021. Based on the hospitalisation date, children in the CR-GNB colonisation group and control groups were matched at a ratio of 1:2. Conditional logistic regression models were used to compute the adjusted odds ratios (aORs) and 95% confidence intervals (CIs) of the risk factors for CR-GNB rectal colonisation in children with HMs. Results A total of 85 non-duplicated CR-GNB isolates were collected from rectal swab samples of 69 children with HMs. The 30-day mortality rates were 5.8% in the CR-GNB colonisation group and 0% in the control group (P = 0.020).colonisation In the conditional logistic regression model, the aORs were 6.84 (95% CI 1.86-25.20) for acute myeloid leukemia (AML) or acute lymphoblastic leukemia (ALL), 4.16 (95% CI 1.17-14.84) for prior concomitant infections within the last 1 month, 2.33 (95% CI 1.16-4.69) for prior carbapenems usage within the last 1 month and 7.46 (95% CI 1.81-30.67) for prior hematopoietic stem-cell transplantation (HSCT). Conclusion AML/ALL, prior concomitant infections within the last 1 month, prior carbapenems usage within the last 1 month, and prior HSCT are associated with an increased risk of rectal colonisation with CR-GNB in children with HMs.